The effects of altitude training on erythropoietic response and hematological variables in adult athletes: A narrative review - Ploszczyca, K.; Langfort, J.; Czuba, M. (Frontiers in Physiology, 2018)
Background: One of the goals of altitude training is to increase blood oxygen-carrying capacity in order to improve sea-level endurance performance in athletes. The elevated erythropoietin (EPO) production in hypoxia is a key factor in the achievement of enhanced hematological variables. The level of the EPO increase and acceleration of erythropoiesis depend on the duration of exposure and degree of hypoxia. Furthermore, many other factors may affect the hematological response to altitude training.